1994
DOI: 10.1542/peds.94.1.29
|View full text |Cite
|
Sign up to set email alerts
|

Simethicone in the Treatment of Infant Colic: A Randomized, Placebo-Controlled, Multicenter Trial

Abstract: Objective. To determine the efficacy of simethicone in the treatment of infant colic. Design. Randomized, double blind, placebo-controlled. Setting. Three general pediatric practices in distinct geographic regions. Patients. Eighty-three infants between 2 and 8 weeks of age with infant colic. Interventions. Treatment with simethicone and placebo in double blind crossover fashion. Results. A total of 166 treatment periods, ranging from 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

1996
1996
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(14 citation statements)
references
References 0 publications
0
13
0
1
Order By: Relevance
“…The interventions included: probiotics/synbiotics (N = 7), maternal dietary interventions (N = 1), preparations containing fennel (N = 3), or other nonprescription remedies (N = 6). Of the 17 studies selected, 12 were randomised controlled trials (15–18,20,41–47) and the remaining 5 were randomised crossover trials (48–52). The randomised crossover trials examined the effects of over the counter remedies including sucrose, glucose, lactase, peppermint, and simethicone.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The interventions included: probiotics/synbiotics (N = 7), maternal dietary interventions (N = 1), preparations containing fennel (N = 3), or other nonprescription remedies (N = 6). Of the 17 studies selected, 12 were randomised controlled trials (15–18,20,41–47) and the remaining 5 were randomised crossover trials (48–52). The randomised crossover trials examined the effects of over the counter remedies including sucrose, glucose, lactase, peppermint, and simethicone.…”
Section: Resultsmentioning
confidence: 99%
“…The Alves et al (49) and Savino et al (17) studies used simethicone as the control intervention, whereas the Metcalf et al (51) study aimed to determine the effect of simethicone on infant colic. The Metcalf et al (51) study found no significant difference when simethicone was compared with a placebo. Interestingly, the Alves et al study (49) showed no differences in the infant's response to the active treatment (peppermint) when compared with simethicone as the control, demonstrating that the treatment and placebo had similar effect.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Obwohl Wirkstoffe wie Simeticon im Vergleich zu Placebo keine signifikanten Unterschiede in der Wirkung zeigen, werden sie verordnet [24]. Die Studienlage zeigt am ehesten bei Einsatz von probiotischen Ergänzungsmitteln wie z.…”
Section: Verhaltensänderungen Und Beruhigungsmöglichkeiten In Reaktionunclassified
“…No medication has definitively proved beneficial in treating infant colic. Two randomised placebo-controlled trials have shown that simethicone is not more effective than placebo (5,6). In spite of the lack of positive results, simethicone is still widely used by physicians.…”
Section: Medicationsmentioning
confidence: 99%